Differences in cardiovascular risk factors associated with sex and gender identity, but not gender expression, in young, healthy cisgender adults - Williams, Jennifer S.; Wiley, Elise; Cheng, Jem L.; Stone, Jenna C.; Bostad, William; Cherubini, Joshua M.; Gibala, Martin J.; Tang, Ada; MacDonald, Maureen J. (Frontiers in Cardiovascular Medicine, 2024)
Background Sex differences exist in cardiovascular disease risk factors including elevated blood pressure and arterial stiffness, and decreased endothelial function in males compared to females. Feminine gender expression may be associated with elevated risk of acute coronary syndrome. However, no study has investigated the associations between sex, gender identity, and gender expression and cardiovascular disease risk factors in young adults. Methods One hundred and thirty participants (22 ± 3 years) underwent assessments of hemodynamics, arterial stiffness [pulse wave velocity (PWV)], and brachial artery endothelial function (flow-mediated dilation; %FMD). Participants completed a questionnaire capturing sex category (50 male/80 female), gender identity category (49 men/79 women/2 non-binary), and aspects of gender expression assessed by the Bem Sex Role Inventory-30 (39 androgynous/33 feminine/29 masculine/29 undifferentiated). Sex/gender identity category groups were compared using unpaired t-tests and gender expression groups compared using one-way ANOVAs. Results Resting systolic and mean arterial pressure (p < 0.01) were elevated in males vs. females. Central PWV was elevated in males [median (interquartile range): 6.4 (1.8) vs. 5.8 (2.2) m/s, p = 0.02]; however, leg and arm PWV were not different between sexes. %FMD was elevated in males vs. females, after accounting for a larger baseline artery diameter in males (8.8 ± 3.3% vs. 7.2 ± 3.1%, p = 0.02); since the majority of participants were cisgender, the same results were found examining gender identity (men vs. women). There were no differences across gender expression groups (p > 0.05). Conclusions Sex/gender identity category, but not gender expression, influence cardiovascular risk factors (blood pressure, arterial stiffness, endothelial function) in cisgender adults; further research is needed in gender-diverse populations.